Dramat jako filozofia dramatu. Na przykładzie twórczości Tadeusza Różewicza - Górska, Irena (Przestrzenie Teorii, 2007)
Tadeusz Różewicz's drama becomes philosophy in two ways. It poses the same questions as philosophy does (about the sense and the aim of human life) and it uses the same methods of expressing itself (it converses with other works, the world, the reader and the writer). Różewicz destroys the old drama rules to re-use them in order to construct some new ones and he rebuilds the world using these rules. However, the newly-built forms don't resemble the classical drama. The boundary between life and art disappears. Paradoxically, it turns out that destruction can be a tool to unite the world. In Różewicz's world everything loses its identity. On the level of genetic rules a fragment appears, whereas, on the philosophical level there is the idea of imperfection.